2009
DOI: 10.1088/0965-0393/17/8/084003
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory calculations of defect energies using supercells

Abstract: Abstract. Reliable calculations of defect properties may be obtained with density functional theory using the supercell approximation. We systematically review the known sources of error and suggest how to perform calculations of defect properties in order to minimize errors. We argue that any analytical error-correction scheme relying on electrostatic considerations is not appropriate to derive reliable defect formation energies, especially not for relaxed geometries. Instead we propose finite size scaling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 42 publications
3
62
0
Order By: Relevance
“…Castleton et al have reported that the contribution of elastic interactions can also be estimated and removed by fitting formation energies obtained using various cell sizes to an appropriate function [56,58,59]. Hine et al have proposed a variant of the Makov-Payne approach, which is applicable to a variety of cell shapes and which eases the extrapolation to the dilute limit by choosing supercells with both positive and negative Madelung energies [60].…”
Section: Electrostatic and Elastic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Castleton et al have reported that the contribution of elastic interactions can also be estimated and removed by fitting formation energies obtained using various cell sizes to an appropriate function [56,58,59]. Hine et al have proposed a variant of the Makov-Payne approach, which is applicable to a variety of cell shapes and which eases the extrapolation to the dilute limit by choosing supercells with both positive and negative Madelung energies [60].…”
Section: Electrostatic and Elastic Interactionsmentioning
confidence: 99%
“…An efficient correction scheme explicitly evaluating the L −3 -dependent term without empirical parameters has been proposed recently by Freysoldt et al [61]. More details on finite-size corrections concerning electrostatic and elastic interactions can be found in recent review articles by Nieminen [62] and Castleton et al [59], as well as in original articles.…”
Section: Electrostatic and Elastic Interactionsmentioning
confidence: 99%
“…25 The formation energies E f for each mass-mediating agent have been computed following the procedure outlined in our previous work, 24 including finite-size scaling. 26,27 Each defect has been considered in its relevant charge state. 24,28 The formation energies are sensitive to the stoichiometry of the material and, in the case of charged defects, also to the Fermi level position l e .…”
Section: B Computational Detailsmentioning
confidence: 99%
“…The Kohn-Sham eigenvalues cannot thus be directly compared to experimental spectra, unlike total-energy differences, yet they provide an important qualitative view of the electronic levels. Therefore, the Kohn-Sham levels should be studied to gain an understanding of the possible stable charge states of the defect before proceeding with total-energy calculations 21 unfortunately, this step is sometimes overlooked, leading to unphysical results.…”
Section: Computational Detailsmentioning
confidence: 99%